Pelatihan Pengolahan Limbah Plastik Warga Rt 02 Pematang Gubernur - Prasetia, Zelinda; Mulyadi, Singgi; Buaton, Wiranda; Meliani, Nita; Danofi, Alwin; Damarsiwi, Eska Prima Monique; Susanti, Neri; Fitriano, Yun (LPPM Universitas Dehasen Bengkulu, 2025)
The continuous increase in plastic waste has become a serious problem in Indonesia, particularly in the RT 02 Pematang Governor area. The lack of awareness and skills among the community in managing inorganic waste, such as plastic bottle caps, has led to the accumulation of garbage and has a negative impact on the environment. This article aims to describe the implementation of a plastic waste processing training program as a solution to the aforementioned problem. The methods used include three stages: preparation of tools and materials, implementation of training in making handicraft products (such as trash bins, pencil cases, and bags of bottle caps), and evaluation and documentation of activities. The training was conducted demonstratively and participatively for the residents of RT 02. The results of the activity show an increase in residents' knowledge, creativity, and skills in recycling waste into valuable and economically useful products. This activity also promotes environmental awareness and the economic independence of the community. In conclusion, creativity-based plastic waste processing training has proven effective as a strategy for implementing a circular economy and sustainable environmental preservation.